Ride with the devil - Woodrell, Daniel 1953-; Danna, Mychael 1958-; Woodrell, Daniel 1953- (<<The>> Criterion Coll., 2010)
In 1862, during the Kansas-Missouri border war, Jake and Jack Bull join the Confederate-sympathizing Bushwhackers after Jack's father is killed by marauding members of the abolitionist Jayhawkers. They are aided by unusual ally, Holt, who's fighting for the South despite being a former slave
Aspect ratio 2.35:1, 16:9 widescreen. - New, restored high-definition digital transfer of Ang Lee's director's cut, supervised and approved by Lee and director of photography Frederick Elmes
Orig.: USA 1999
Enth. two audio commentaries, one featuring Lee and producer-screenwriter James Schamus, and one featuring Elmes, sound designer Drew Kunin, and production designer Mark Friedberg ; new video interview with star Jeffrey Wright ; a booklet featuring essays by critic Godfrey Cheshire and Edward E. Leslie, author of "The devil knows how to ride : The true story of William Clarke Quantrill and his confederate raiders
Keywords: Woodrell, Daniel -- Film adaptations.; Woodrell, Daniel -- Television adaptations.; Woodrell, Daniel -- 1953-; War films.; Feature films.; Kriegsfilm; Sezessionskrieg -- 1861-1865; Verfilmung; Film; DVD-Video